PENGARUH KEMAMPUAN KERJA PEGAWAI DAN KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT DALAM MENERIMA PELAYANAN PUBLIK DI KECAMATAN KARAWACI KOTA TANGERANG - Wicaksono, Elga Nor; ., Nursusanto; Dahlan, Jarnawi Afgani (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2020)
This study aims to determine and explain the effect of employee work ability and quality of service to public satisfaction in receiving public service at Karawaci District Tangerang City. For his research is the capability of the variable (X1), quality of service (X2) and community satisfaction (Y). The research method used is a quantitative method with an associative type that explains the relationship between independent variables with the dependent variable. The survey was conducted on 100 communities receiving services in Kecamatan Karawaci Tangerang City from the total community as many as 132,617 people over the age of 18 years and literature study as a supporter of empirical study. Hypothesis testing is done through data processing using SPSS for Windows program package version 20.00 year 2013 with static correlation analysis method, determination coefficient and linear regression. The validity of the instrument is done through validity, realibility, normality and linearity of data. Based on the analysis result, it can be concluded that the ability of employee's ability to influence the satisfaction of the community in Kecamatan Karawaci amounted to 32.95%. The ability of service quality in influencing community satisfaction in Kecamatan Karawaci amounted to 44.22%. The ability of employee job satisfaction and service quality in influencing the community satisfaction in Kecamatan Karawaci amounted to 52.00%. Suggestion from this research is Head of Karawaci must pay more attention to the dimensions in research variables so that public satisfaction in receiving public service in Kecamatan Karawaci can be improved. In addition, the evaluation of community satisfaction with the acceptance of the public service should be performed regularly with the parameters that are tailored to the Regulation of the Minister of Administrative Reform and Bureaucratic Reform No. 16 Year 2014 on Guidelines for Public Satisfaction Survey Of Public Service Operator.